Manajemen Pembukuan pada Petani di Desa Adat Anggabaya - Ni Nyoman Ayu Suryandari; Cokorda Javandira; I Made Suryana; I Made Suparsa (WIDYABHAKTI Jurnal Ilmiah Populer, 2021)
Anggabaya Traditional Village has natural resources and wide and good agricultural land. Farmers in the Anggabaya Traditional Village are members of an organization called Subak. In managing their farming business, most of the farmers in the Desa Adat Anggabaya still have problems because there are still many farmers who do not know how to make a format for recording financial transactions and apply simple bookkeeping. Bookkeeping management training is expected to be able to solve the problems experienced by farmers so that farmers can make their own books and know the cash inflow and outflow of cash every time they make a purchase or sale transaction.